If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -6y + -9y + 11x + 3 = 0 Reorder the terms: 3 + 2x + 11x + -6y + -9y = 0 Combine like terms: 2x + 11x = 13x 3 + 13x + -6y + -9y = 0 Combine like terms: -6y + -9y = -15y 3 + 13x + -15y = 0 Solving 3 + 13x + -15y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + 13x + -3 + -15y = 0 + -3 Reorder the terms: 3 + -3 + 13x + -15y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 13x + -15y = 0 + -3 13x + -15y = 0 + -3 Combine like terms: 0 + -3 = -3 13x + -15y = -3 Add '15y' to each side of the equation. 13x + -15y + 15y = -3 + 15y Combine like terms: -15y + 15y = 0 13x + 0 = -3 + 15y 13x = -3 + 15y Divide each side by '13'. x = -0.2307692308 + 1.153846154y Simplifying x = -0.2307692308 + 1.153846154y
| -2(-10)-3= | | -2-10-3= | | (a-5)(3a+2)(a+5)= | | 6(-5x)=5x-3 | | (2x+1)(x^2-2x-3)= | | x^5+x^4+x^3+x^2+x-383=0 | | -16x^2+32x= | | (5-u)(5u-4)= | | 2x-5(x-4)=-9+5x+5 | | 7.25n=116 | | 10.73+n=26.73 | | T/2=56 | | -2(c-3)=4(d+6) | | 9x-8y=222 | | 54+19m=187 | | 26n-72=396 | | 20x+25y=22 | | X=(6x-3)10 | | 2x-(3-6x)2= | | e^4x+3e^2x-10=0 | | 5B+4B=90 | | 5x-2(x-5)=-8+5x+6 | | 4x+132=7x+257 | | -1/7(7-14x)=11 | | M+m+2m-3m=11 | | 4p-p+4p-5p-p=17 | | (5x-1)(6x+8)=0 | | 152+15m=407 | | 32n-171=437 | | 9u-8u=16 | | 7(6+8)=t-4+2 | | .25z=2.75 |